(untitled) (Journal of the College of Education for Women, 2019)
The Al-Shishtary is considered one of the well-known Andalus poets. His poetry represents a flood of kind emotions, springs from the sincere sources of Divine Love, and this is what we felt in his life and his literary prestige. He was a poet who was familiar withthe art of his timeknowsthe oldand popularintellectual assets ofIslamicSciencesof Sharee’a. This wide culture, which he had, is available to him through his many travels between the coasts of Syria, Egypt and others ... to become Imam of the religion way known as(Al-Shishtariyah)resonatedin the hearts ofthe general publicespecially the poor people. This showshis smoothand influential styleand his humanitarian andsimple words which resonate in the hearts of his followers, therefore, his poems remained until this day inheritedbyChadli inEgypt.Al-Shishtary was the pioneer in theuseof(Zajal)inSophism and he acquired the title of Sophist philosophic poet and the owner of Alazjal. The researcher tackles thesubjectofthenarrativeconstructionin Al-Shishtary poetryanddeals with its manifestations and mechanisms in terms of: - Poetic language and its functions, especially it provides artistic modalities of sayings in order for the receiver to access the message targeted to him. These functions appeared in his poetryas follows: - emotional function - poetic function - reference function - Function of understanding and listening At the end, the researcher talks about (description) within the narrative construction that mastered the dimensions of the technical image temporally and spatially. The researcher has allocated two types of description, they are as follows: - Description which revealed the features and the external traits of the characters. - Description which deals with the disclosure of the psychological worlds of the characters. This paper, also deals with the dialogue that has been or took place between the characters of his artistic work, having been employed in his narrative artistic in a highly literary manner. Then, the repetition instances and the overlapping of tenses have been located in the construction of event inside the narrative space taking into consideration the time and place and revealing their impact in the narratives of Al-Shishtary throughout separating the tenses and dividing them into: general tense, anticipated tense and revocation tense, as well as places which have been classified within the space narrative construction into familiar places and hostile places and its impact on the psyche of the narrator and receiver alike. At the end of the research the researcher puts the conclusion of research and its findings, and list of sources and references and summary in English.